Evaluation of 99mTc-Ethambutol Radiopharmaceutical Using High Performance Liquid Chromatography with Radioactive Detector (Radio-HPLC) - Maula Eka Sriyani; Rizky Juwita Sugiharti; Eva Maria Widyasari; Iim Halimah (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
99mTc-ethambutol is a radiopharmaceuticals used to determine the location of Mycobacterium tuberculosisthat causes TB disease. To prepare this radiopharmaceuticals, several supporting compounds are required in addition to ethambutol and radionuclide compounds. These are mannitol as filler, SnCl2as a reducing agent and sodium pyrophosphate as co-ligand. The radiopharmaceuticals is made in the form of a lyophilized kit without 99mTc radionuclides. The aim of this study was to determined the effect of reducing agents on 99mTc-ethambutol preparation using the High Performance liquid chromatography (HPLC) equiped with radiodetector (radio-HPLC) to the quality of radiopharmaceuticals. In the previous study, the determination of radiochemical purity only used TLC by determining the amount of impurities TcO2and TcO4. This study was carried out more profoundly by using radio-HPLC to ensure the quality of radiopharmaceutical products that were made is actually 99mTc-ethambutol. The Test were performed using paper chromatography, electrophoresis, radio-HPLC, and stability test of 99mTc-ethambutol radiopharmaceuticals. The results showed that the radiopharmaceuticalkit of ethambutol is performing good physical characterictics and high radiochemical purity of 99mTc-ethambutol both in analysis using paper chromatography, electrophoresis and radio-HPLC. The 99mTc-ethambutol shown the peak at retention time (tr) 7,97 minutes using UV and radioactive detector, C18 column, isocratic system using phosphate buffer 0,2 M pH 7,4 and Acetonitrile (90 :10), flow rate 0,8 mL/min. The radiochemical purity of 99mTc-ethambutol is still remain high (91.44 ± 0.92%) after 27 days of kit were made.Key words: 99mTc-ethambutol, radio-HPLC, TB disease, Mycobacterium tuberculosis, radiopharmaceuticals.